Chilling-Like Attacks Terminated by Slow Pathway Ablation - Yetkin, Gulay; Ozturk, Selcuk; Yetkin, Ertan (Current Cardiology Reviews, 2020)
Symptoms of patients or the way of presenting complaints by the patients may be indefinite, obscure or misleading for the diagnosis of supraventricular tachycardia. The content of the history shows variability depending on the present symptoms, patient concerns and priority. Herein, an unusual case of a young woman suffering from chilling-like attacks for one and half years and treated by slow pathway ablation has been presented.
Keywords: cardiac innervation